TRENDS IN TOURIST FLOWS DURING THE PANDEMIC - BLAHUN, Ivan; RUMIANTSEVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The existence of certain cyclical fluctuations and periods of slowdown, primarily associated with the economic crisis at the end of the first decade of the 21st century, does not change the fact that the demand for tourist services in the world developed at a high rate during the analyzed period. The article analyzes according to data from the UN World Tourism Organization (UNWTO), that in 2020 the number of international tourists decreased by 73%, or by 1.1 billion people. It was noted that in 2020, revenues from international tourism exports also fell by 63%, or $1.1 trillion USA. The direct contribution of tourism to the world GDP decreased by 2000 billion dollars. USA. International tourist arrivals in 2021 are shown to be down 72% or 1 billion people from 2019 and up 4% or 15 million people from 2020. A decrease in indicators of the dynamics of the development of international tourism was revealed. Due to the global economic recession and general geopolitical and social tensions in the world, as well as due to COVID-19. Negative global trends had a negative impact on tourist flows in general and the work of international travel agencies. It has been proven that the 73% drop in international tourism in 2020 was due to travel restrictions, tourists' concerns about the pandemic situation and the global fight against the coronavirus.The trends in the development of international tourism in 2000-2021 have been studied and presented in detail. in the pre-pandemic period and during the COVID-19 pandemic. Іt has been proven that the tourism industry has suffered great losses due to the COVID-19 pandemic, as this pandemic has become the biggest challenge of 2020 and continues to have a negative impact not only on tourism, but also in general to intensify the economic and social crisis in the world. This is evidenced by the number of arrivals. 415 million international arrivals were registered globally in 2021, up from 400 million in 2020. After a weak first half of 2021, international tourism recovered moderately in the second half. Confirmed growth in demand in 2021 was driven by improved traveller confidence amid rapid vaccination progress and easing of entry restrictions in many destinations. The problems and opportunities that may arise in the tourism industry in the coming years have been studied.
Keywords: tourist demand; international tourism; tourist arrivals; international tourism development trends; tourist services market; tourist; tourist products; tourist flows; pandemic; COVID-19